Re-visioning resurrection: St. Paul and Swedenborg - Avens, Roberts (Journal of religion and health, 1984)
St. Paul's "spiritual body" is envisaged as imaginal body, the wordimaginal standing for the intermediate realm of beings and events in Neoplatonism and Sufism. Swedenborg's world of spirits and angels conforms to this view and so is seen as contributing to a richer understanding of St. Paul in the sense of a "good" docetism. Crucial in this kind of revisioning the mystery of resurrection is the creative power of visionary imagination, which, in turn, is inseparable from the reality of the soul as thesitus of visionary events.